Intellectual property rights usage for academic entrepreneurship among Business Educators in Universities within Rivers State, Nigeria - Benibo, Opuda Sunday; Bupo, Godwin Omoni (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
The study investigated the utilization of intellectual property rights for academic entrepreneurship among Business Educators in Universities in Rivers State. The study made use of two specific objectives, two research questions and two hypotheses. A survey design was adopted for the study. A total of 48 Business Educators in the three public Universities in Rivers State made up the population. No sampling technique was used since the population of the study is of manageable size. A self-structured instrument validated by three experts in the relevant areas was used for data collection; however, only 46 questionnaires were retrieved and used for the study. Mean and standard deviation were used to analyze the data, and Analysis of Variance was used to test the hypotheses formulated for the study at a 0.05 level of significance. The findings of the study revealed that Business Educators' extent of utilization of intellectual property rights for academic entrepreneurship is generally low. Therefore, it recommends amongst others that University management should provide resources and comprehensive training on intellectual property rights to raise awareness and encourage academic researchers to utilize these rights. The government should provide incentives such as tax credits or advanced market commitments to encourage academic researchers to obtain and utilize intellectual property rights.